Duration of Maternal Stress and Depression: Predictors of Newborn Admission to Neonatal Intensive Care Unit and Postpartum Depression. Issue 5 (September 2015) - Latendresse, Gwen; Wong, Bob; Dyer, Jane; Wilson, Barbara; Baksh, Laurie; Hogue, Carol
Abstract : Background: Maternal psychosocial factors contribute to adverse pregnancy outcome, but very few studies have assessed associations of duration and experiences of stress, depression, and intimate partner violence (IPV) with maternal and newborn outcomes. Objectives: It was hypothesized that duration and level of maternal stress, depression, and IPV would predict increased risk of adverse maternal/newborn outcomes. Methods: A secondary data analysis of a population-based data set collected by the Utah Department of Health Pregnancy Risk Assessment and Monitoring System and birth certificates for 4682 live births was conducted, reflecting a total population size of 143, 373 live births in 2009–2011. Exposures of interest were experiences and duration of maternal stress, depression, and IPV before and during pregnancy. Outcomes were gestational age, birth weight, newborn admission to the neonatal intensive care unit (NICU), and postpartum depression (PPD) symptoms and diagnosis. Results: After controlling for maternal demographics, body mass index, and smoking, women with greater duration of depression before and during pregnancy showed an increase in admission of their newborn to NICU (adjusted odds ratios [a OR s] = 1.66–2.48, p < .001), PPD symptoms (a OR s = 3.94–9.13, p < .001), and diagnosis of PPD (a OR s = 7.72–59.60, p < .001). More kinds of experiences of maternal stress were associated with higher odds of PPD symptoms (a OR s = 1.34–5.51, p < .001), but not PPD diagnosis or NICU admissions. Discussion: Longer lasting maternal depression and stress are associated with poorer outcomes for mothers and newborns. Future prospective studies should evaluate the usefulness of preconception and continuous prenatal risk identification of maternal depression and stress. This would facilitate timely psychosocial interventions as an approach to improving maternal/newborn outcomes for these higher risk women.